Psychosocial Effects of Receiving Genome-Wide Polygenic Risk Information Concerning Type 2 Diabetes and Coronary Heart Disease: A Randomized Controlled Trial - Halmesvaara, Otto; Vornanen, Marleena; Kääriäinen, Helena; Perola, Markus; Kristiansson, Kati; Konttinen, Hanna (Frontiers in Genetics, 2022)
Receiving polygenic risk estimates of future disease through health care or direct-to-consumer companies is expected to become more common in the coming decades. However, only a limited number of studies have examined if such estimates might evoke an adverse psychosocial reaction in receivers. The present study utilized data from a sub-section of a personalized medicine project (the P5 study) that combines genomic and traditional health data to evaluate participants’ risk for certain common diseases. We investigated how communication of future disease risk estimates related to type 2 diabetes and coronary heart disease influenced respondents' risk perception, self-efficacy, disease-related worry, and other emotions. A randomized controlled trial was conducted, where the experimental group (n = 714) received risk estimates based on traditional and polygenic risk factors and the control group (n = 649) based solely on traditional risk factors. On average, higher disease risk was associated with higher perceived risk (ps, <.001, ηₚ² = 0.087-0.071), worry (ps <.001, ηₚ² = 0.061-0.028), lower self-efficacy (p <.001, ηₚ² = 0.012), less positive emotions (ps <.04, ηₚ² = 0.042-0.005), and more negative emotions (ps <.048, ηₚ² = 0.062-0.006). However, we found no evidence that adding the polygenic risk to complement the more traditional risk factors would induce any substantive psychosocial harm to the recipients (ps >.06).